Russian Natural Gas Exports to Europe. Effects of Russian gas market reforms and the rising market power of Gazprom - Eirik Lund Sagen; Marina Tsygankova (Statistics Norway, Research Department, 2006)
Gazprom, the dominant gas company in Russia, is widely believed to be the key supplier of gas to Europe in the foreseeable future. However, there are numerous uncertainties and challenges within the Russian and European gas industry that may alter the allocation of Gazproms gas sales between domestic and export markets. In this paper we use both theoretical and numerical models to study potential effects on Russian gas exports from changes in Russian domestic gas prices and the production capacities in 2015. We also investigate whether the liberalization of the European gas markets may provide incentives for Gazprom to induce monopoly power in its export markets. Our main findings suggest that both increased domestic gas prices and sufficient production capacities are vital to maintain Gazproms market share in Europe over the next decade. At low domestic prices, Gazprom may even have difficulties to carry out its long-term export commitments. However, if export possibilities are ample due to both lower domestic demand at higher prices and high overall production capacities, a large share of spot trades in Europe may encourage Gazprom to exercise market power in its export markets.
Keywords: F17; D42; Q31; Q38; 330; Russia; Natural gas; production capacity; export; Western Europe; price; numerical model